Cognitive Habitat, Strategy Ecosystem: A Predictive Model of Emergence for Cognitive and Computer Science - Dominicus Tornqvist (IEEE, 2021)
Cognitive research has found people are sometimes adept and sometimes inept at handling complexity. Complexity is a key concept in much of cognitive science, yet the field has scarcely incorporated any of the work in complexity theory. Complexity theory may generally be too abstract to easily apply to human cognition studies. Here, the problem is addressed by considering complexity through constructing a model of epistemic emergence, Cognitive-Habitat Strategy-Ecosystem, (CHSE) to act as an overarching framework into which different conceptions of complexity and cognition can be integrated, describing how they will interact to affect cognition in complex systems. This model provides value both at the micro level, by generating specific predictions, and at the macro level, through hypothesizing interactions between other cognitive theories such as cognitive load and adaptation from failure. We detail the model’s assumptions, functionality, and possible ways to measure variables.